UJI KELAYAKAN KIT PRAKTIKUM PENGUJIAN KEPOLARAN SENYAWA DARI MATERIAL SEDERHANA - Robby Zidny; Dirayati Yusrina; Intan Aryoningtyas; Nur Indah Elvina; Mamah Halimah; Novi Dwi Ayuni; Yanti Hadiyati (Jurnal Riset Pendidikan Kimia (JRPK), 2017)
This study aims to validate the feasibility of chemistry lab kit made from simple materials on the concept of chemical compounds polarity for high school students in remote areas. Educational research and development model includes needs assessment, product design, expert validity test and limited scale test used in this research. The research instrument used in the form of a questionnaire aimed to test the validity of experts analyzed using Likert scale. A limited scale test conducted on 20 students of 10th grade SMA Negeri 1 Pamarayan Serang to find out the feasibility and practical aspects of the tool. Respondents' opinion on the products obtained through questionnaires and analyzed using descriptive analysis by making the percentage scale of each statement on the questionnaire. The results showed the profile of the chemistry lab kit of chemical compounds polarity made of wood, plastic bottles and magnets with a total mass of Â± 0.8 Kg. Based on the results of assessment analysis and validation of experts in the field of education obtained an average assessment of feasibility aspects of 77.50% included in good category. Analysis of the students' assessment of the practicality of the lab kit obtained an average value of 86.6% which is included in the category of very good. While the results of student responses in some aspects of the lab kit in the learning proccess obtained average value of 76.1% in the category good. The lab kit also facilitate students to understand the test of compounds polarity based on the ability to answer questions which obtained average score of 85.55 in the category of excellent. Keywords: Chemistry lab kit, Chemical compound polarity, Simple Materials